The Role of Local Wisdom Integrated Worksheets in Strengthening Students' Environmental Awareness - Syarkiah Amaliah, Mutahharah Hasyim*, M.A. Martawijaya, Muhammad Taqwin (Journal of Physics Education : Review and Research, 2024)
The Role of Local Wisdom Integrated Worksheets in Strengthening Students' Environmental Awareness. The purpose of this study is to determine the ability of students to write ideas by utilizing physics concepts to care for the environment. This research was carried out at SMA Negeri 5 Sidrap and the location of Blacksmith with the research subjects of 3 students in class XI MIPA 1 SMA Negeri 5 Sidrap. The test subjects are students who like to learn physics and are considered less concerned about the environment. Research instruments used by human instruments. The data collection techniques used are observation, written tests, and unstructured interviews. The worksheet was designed by referring to local wisdom in Sidrap with the object "Blacksmith (Pallanro Bessi)". The results of initial observations before testing this physics worksheet that integrates local wisdom, there were 3 students who were not happy to learn physics and did not care about the environment. After conducting a Worksheet trial, they have written down ideas to care for the environment, but the idea still lacks the physics concepts they have.